CARACTERIZAÇÃO BIOGEOQUÍMICA DA MATÉRIA ORGÂNICA NO ESTUÁRIO DO RIO PACIÊNCIA, MA. - PEREIRA, Valléria Vieira (2021)
Due to the great diversity of sources of organic matter (OM) and the dynamic mixing that occurs in estuarine systems, it is a significant challenge to determine the relative importance of these input sources for biogeochemical cycling in the water column and in sediments. Estuaries can function as a retainer or as an exporter of organic material and considering that this material has unstable characteristics, it is necessary to use a combination of techniques that may include methods of studying the elemental and isotopic composition, biochemical tracers and biomarkers. In order to assess the origin of OM for the Rio Paciência Estuary (RPE) - MA, Brazil, quantifying the contribution of autochthonous and allochthonous sources and evaluating the processes that rule the distribution of organic matter in the sediment, 2 campaigns were performed during the periods of drought (Nov/2017 and Nov/2019) and 1 in the rainy season (Apr/2018) to collect surface sediment, suspended particulate matter (SPM) and plant tissues from two mangrove species found in the RPE, A. germinans and L. racemosa, to perform particle size analysis, surface area analysis, elemental determination [organic carbon, total nitrogen, atomic carbon (C) and nitrogen (N) ratio [(C / N) a] and isotopic ratios of C (δ 13C) and N (δ 15N)]. The physical-chemical characterization of the water was performed with the assistance of a refractometer and an oxygen and temperature meter. The SPM was separated using a gravimetric method. The superficial sediments were collected on the left margin of the ERP with the aid of a plastic spatula. The granulometric analysis was performed on a Particle Size Analyzer (SALD 3101, Shimadzu). The analysis of the surface area (SA) was performed in a surface area analyzer (NOVA QUANTACROME 1200). For elemental and isotopic determination, an Elemental Analyzer coupled to a Delta V Advantage Mass Spectrometer was used. For the purpose of characterize the OM sources to the surface sediments and for the SPM the SIMMR (Stable Isotope Mixing Models in R) mixture model was applied. The results showed a predominance of fine material in the region, mostly in clay size (71.2%), it was also evidenced some points with the presence of sand in the portion of the ERP with greater marine influence. The ratio values (C / N)a of the MPS (ranging between 5 and 9) and sediment samples (ranging between 11 and 9), as well as the isotopic signatures, indicates that the OM is composed by a mixture of terrestrial and marine sources. The values of δ 13C and δ 15N showed that the organic matter in the MPS (δ 13C: from -28,2‰ to -24,2‰; δ 15N: 2,2‰ to 7,9‰) and in the superficial sediments (δ 13C: -27,6‰ to -25,6‰; δ 15N: from 4,1‰ to 6,3‰) is composed of a mixture of marine sources, such as phytoplankton, and terrestrial sources, C3 plants, with seasonal changes in the contribution of possible sources.